Effect of acetone on physical properties of PES membrane - Ahmed, I. (Trans Tech Publications Ltd, 2014)
In the present study, polyethersulfone (PES) dope solution were prepared from mixtures of two solvents containing dimethylformamide (DMF) as core solvent, and acetone as co-solvent (CS), deionized water was used as coagulant bath. The amount of PES was kept at 20 wt and the weight ratios of acetone were varied 20-24 wt. to DMF and the dope solutions were prepared under closed heating system Results revealed the complete miscibility of PES with the fixed mixture of acetone and DMF under atmospheric pressure. The relationships between degree of adsorption, relative water absorption, were investigated. The results revealed that the interaction of DMF and acetone is strongest when their mole ratio is unity, which exhibit the phenomenon of true cosolvency for PES membrane. Â© 2014 Trans Tech Publications, Switzerland.